The Influence of Service Quality and Price on Customer Satisfaction and Its Impact on Customer Loyalty at BRILink Agent PD. Devisma - Nurazizah, Devianti; Hamdani, Nizar Alam; Cupiadi, Hedi (Entrepreneurship Faculty, Universitas Garut, 2024)
Agen BRILink PD. Devisma, operating in the area of Kantor Unit BRI Samarang Cabang Garut, provides various banking services through BRI mini ATM EDC or BRILink Mobile. The objective of this study is to analyze the effect of service quality and price on customer satisfaction and its impact on customer loyalty at Agen BRILink PD. Devisma. This study employs a quantitative research method using a questionnaire distributed via Google Form to 97 respondents who have conducted transactions at least twice at Agen BRILink PD. Devisma. Data analysis is performed using Structural Equation Modeling (SEM) with Partial Least Square (PLS) technique using SmartPLS 3.0 software. The results of the study indicate that the overall responses of respondents towards service quality, price, customer satisfaction, and customer loyalty fall into the good category. Hypothesis testing shows that service quality and price positively affect customer satisfaction, customer satisfaction positively affects customer loyalty, and service quality positively affects customer loyalty. However, price does not affect customer loyalty, as it is considered higher compared to its competitors. Keywords: Service Quality; Price; Customer Satisfaction; Customer Loyalty